Thermomechanical analysis of coal ash fusion behavior. (22nd June 2016) - Yan, Tinggui; Kong, Lingxue; Bai, Jin; Bai, Zongqing; Li, Wen
Abstract: Ash fusion behavior relates to several key issues for designing and running boilers or gasifiers, including fouling, sintering or slagging. In order to illustrate the mechanism of ash fusion behavior, the ash fusion temperature test, thermomechanical analysis (TMA), the high temperature processing microscope (HTPM) and differential scanning calorimetry (DSC) were applied to describe the ash fusion process and the characteristics of fusion temperatures. In addition, the thermodynamic software FactSage™ was used to reveal the relation between liquid phase formation and ash fusion behaviors. The shrinkage trace by TMA not only indicated the ash fusion temperatures, but also described the fusion process quantitatively. The ash fusion process can be divided into sintering, primary fusion and the free liquid stage based on the shrinkage trace, which was supported by HTPM and DSC results. Stage I (sintering stage), in which sintering was initialized by the formation of an initial eutectic, was characterized as the liquid phase sintering stage. The initial temperature of sintering stage is essential to prevent ash sintering or fouling. In stage II (primary fusion stage), most of the solid minerals melted and the formation rate of the liquid phase reached its maximum. The range of the plateau in this stage is determined by the end points of sintering and newly formed eutectics. During stage III (free liquid stage), the remaining solids dissolved in the liquid slag and influenced the flow behavior of slag at high temperatures. Overall, the ash fusion mechanism "Sintering-fusion-dissolving" was proposed according to the fusion behavior. The end points of the sintering and primary stage, denoted as T s1 and T s2, agreed well with deformation temperature and flow temperature, respectively. T s1 or deformation temperature should be used as key criteria to prevent sintering in boilers and gasifiers. Highlights: Coal ash fusion behavior is firstly investigated by multiple methods and divided into three stages. The ash fusion mechanism "Sintering-fusion-dissolving" is raised according to the coal ash fusion behavior. T s1 from TMA trace is the end of ash sintering and should be used as criteria to prevent sintering.